Burundi : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This Selected Issues paper on Burundi highlights that after the Arusha Peace Agreement in 2000 Burundi has faced a wide range of challenges to generate sustained and equitable economic growth and improve social conditions. Burundi has begun to stabilize the economy, liberalized the trade and exchange regimes, reformed monetary policy, and taken steps to reinforce public financial management. GDP growth has been high during the program, except in 2005, when drought and floods reduced growth to about 1 percent of GDP.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet